Kajian Sifat Organoleptik Dan Daya Terima Es Krim Jalor (Jambu Biji Dan Sari Daun Kelor) - Nadya Natasya (Jurnal Gizi Prima (Prime Nutrition Journal), 2019)
Background: Young women generally have characteristics of unhealthy meal habits and many of them lack of nutrients needed, so there is a need to have an alternative nutritionally rich and attractive food product through the manufacture of JALOR Ice Cream which is produced from Milk, Guava and Moringa Leaf Extract, to increase iron in order to prevent iron deficiency.Methods: This study was conducted using an experimental research design. The experiment was carried out using a Completely Randomized Design (CRD) using 5 treatments with the addition of Moringa Leaf Extract: t1 (10%), t2 (20%), t3 (30%), t4 (40%) and t5 (50%). The experiment were carried out on hedonic tests on 20 panelists with 5 scales, namely: 5 = Very like, 4 = Like, 3 = Neutral, 2 = Dislike, and 1 = Very dislike. Acceptance test was conducted on young women.Result: The results of the organoleptic test showed that JALOR Ice Cream was chosen on treatment t2 with the addition of 20% Moringa Leaf Extract. The results of the adolescent girls' acceptance of selected JALOR Ice Cream products showed that all (100%) panelists were at the level of good category.Conclusion: JALOR Ice Cream is with the addition of 20% Moringa Leaf Extract is the most preffered. The acceptance of Ice Cream can be well received by panelists.